The Islamic Accounting Conception for Islamic Management Entities through Scrutinising the Islamic Epistemological Stances - Aziz, Norazita Marina Abdul; Ahmad, Fadzila Azni (International Journal of Engineering and Technology, 2018)
The conceptualisation of Islamic accounting considers various dimensions including social benefit, social justice, sincerity, loyalty and trustworthiness. The recognition of social well-being reflects the eternal relations of mankind to Allah SWT and the interconnection to other human beings. The social obligations and engagements derives from the ‘closeness’ within the social-relations. Consequently, the paper examines the conceptualisation of the Islamic accounting framework from the Islamic philosophy perspectives and investigate the applicability of Islamic accounting concepts in recording Islamic transactions for Islamic management entities. The study employs interpretive epistemological position from Grounded Theory research design. The fieldwork involves interviews of five informants. Additionally, the documentary review were evaluated through the interpretation of the absolute scripts from al-Quran, Hadiths and other related Islamic manuscripts. The interviews are conducted to gain in-depth insights and investigate the emergence details in contemplating the research objectives. The data is analysed through exhaustive content analysis to obtain a new emergence concepts and thick data descriptions. The findings reveals the Islamic accounting concepts encompasses ‘tauhidic’ position, the intensification of the social and economic welfare and internal values of individual. The actions for accomplishing sufficient security of wealth has to be engrossed in the fair sharing of Islamic wealth (waqf and zakat), considered lawful activities and undertaken meticulous operationalization strategies. In summary, the paper suggests comprehensive monitoring and distribution of wealth through Islamic assets management systems.